From yaad to abroad : "a young Jamaican's story of survival, manhood and success" : the story of the country boy in a big city - Antonio, Kaz (Jamaica, St. James (Montego Bay) : Casana Spence, 2016)
Coming-of-age novel about a young Jamaican boy determined to make a better life in England.
NLJCols20082021
Keywords: Jamaicans -- England -- Fiction; Blacks -- England -- Fiction; Success -- Psychological aspects -- Fiction; Bildungsromans; Jamaicans; Blacks; Bildungsromans; Jamaican fiction; Short stories, Jamaican; Success -- Psychological aspects; England; Fiction; Jamaican fiction -- Black authors -- 21st century